Factors Affecting the Competitiveness of Logistics Service Enterprises: A Case Study of Dong Nai Province - Nguyen Viet Hung; Phan Thanh Tam (International Journal of Supply Chain Management, 2021)
Competitiveness of enterprises can maintain and improve competitive advantage in consuming products or services. Besides, enterprises expanded their consumption network through surveying experiences in the logistics service sector. Therefore, the authors surveyed 30 logistics service enterprises with 500 customers. The results showed five factors that affected the competitiveness of logistics service enterprises of Dong Nai Province with 1% significance. Finally, the article draws some recommendations to help enterprises improve the competitiveness of logistics services